2017
DOI: 10.1016/j.bbmt.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Hematopoietic Cell Transplantation Using Treosulfan-Based Conditioning for Treatment of Marrow Failure Disorders

Abstract: Hematopoietic cell transplantation (HCT) is effective in the treatment of inherited marrow failure disorders and other non-malignant diseases. Conventional myeloablative conditioning regimens have been associated with high transplant related mortality particularly in patients with co-morbid conditions. Here we report on 14 patients with marrow failure disorders (Shwachman-Diamond syndrome n=3, Diamond Blackfan anemia n=4, GATA2 deficiency n=2, paroxysmal nocturnal hemoglobinuria n=4, and an undefined marrow fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…After initial data on treosulfan-based conditioning in adult alloHSCT patients became available [9,10], several published studies reported on the efficacy and safety of treosulfan given as part of various conditioning regimens in children [12,13,15,16,20,31]. Here, we report the final results of the first prospective alloHSCT trial of a treosulfan/fludarabine/thiotepa combination regimen (FTT; 65 of 70 trial patients treated) administered to children and adolescents with hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After initial data on treosulfan-based conditioning in adult alloHSCT patients became available [9,10], several published studies reported on the efficacy and safety of treosulfan given as part of various conditioning regimens in children [12,13,15,16,20,31]. Here, we report the final results of the first prospective alloHSCT trial of a treosulfan/fludarabine/thiotepa combination regimen (FTT; 65 of 70 trial patients treated) administered to children and adolescents with hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies, including prospective phase III trials in adults with AML and MDS, have shown that treosulfan-based conditioning has myeloablative, immunosuppressive, and antineoplastic effects associated with a low non-relapse mortality (NRM) [6][7][8][9][10][11]. Furthermore, several reports have been published that show an indication for treosulfan-based conditioning in children undergoing alloHSCT for nonmalignant and malignant disorders [12][13][14][15][16][17][18][19][20][21]. In addition, pharmacokinetic (PK) investigations on treosulfan in children have been conducted in order to derive dose recommendations for all pediatric age groups [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Our results about the remarkable strong association between early increase of complement activation (as reflected by sC5b-9 levels) and later development of TA-TMA are in line with this model. Therefore, due to the high proportion of treosulfanbased conditioning regimens (24 of 33) in our cohort the rate of significant early transplant-related complications was reasonably low [32][33][34], and nonrelapse mortality did not associate with TA-TMA (Table 1). After more aggressive or toxic conditioning regimens, more severe TA-TMA cases could be observed, and further studies would be needed to validate these observations on adult and on other conditioning regimen cohorts.…”
Section: Discussionmentioning
confidence: 89%
“…Conditioning. An international expert panel recommended the use of either busulfan-or treosulfan-based myeloablative conditioning, for bone marrow failure disorders (Parikh et al, 2014;Peffault de Latour et al, 2015;Burroughs et al, 2017). All recommendations are based on small case series.…”
Section: Haematopoietic Stem Cell Transplantationmentioning
confidence: 99%